Biased perception misguided by affect: How does emotional experience lead to incorrect judgments about environmental quality?. (November 2018) - Yang, Jianxun; Zhou, Qi; Liu, Xingyu; Liu, Miaomiao; Qu, Shen; Bi, Jun
Graphical abstract: Highlights: Psychophysiological study was introduced to study environmental risk perception based on emotion science. Both self-reported and physiological data demonstrated people were capable to detect surrounding air quality. Public perception of air quality was misguided by negative emotional experience. The government ought to take account of the tricky role of emotion when communicating environmental risks. Abstract: Understanding how the lay public judge air pollution is of high significance for creating effective pollution control targets in China. Emotion theories have great potential to advance relevant knowledge. Taking advantage of an environmental psychophysiological experiment in Nanjing, China, this study uncovers the underlying mechanism of why Chinese people have a biased perception towards improved air quality. The results from both self-report and physiological data first demonstrated individuals' emotional habituation to their surrounding pollution level. The participants were prone to have the most neutral emotional responses at around 42 μg/m 3 PM2.5 concentration, which matched well with the average PM2.5 concentrations of daylight hours in Nanjing. As PM2.5 pollution improved (worsened), participants' pleasant (unpleasant) visceral reactions were thereby intensified. However, due to the Peak-end Rule, some extreme emotional experiences caused by heavily PM2.5 -polluted events in winter may overwhelm the public memory. Such negative emotions lead to incorrect judgments about overall improved air quality. The results also showed that people lacked defensive motivational arousal towards bad air quality. We suggest that the government should pay more attention to avoiding the "Peak" effect of heavily polluted weather, and promote individual adaptive behaviors. To our best knowledge, this is the first research introducing a psychological experiment into the perception study of air pollution. Great opportunity exists to further extend this novel method into understanding other environmental issues.